EFFECT OF DEBT TO EQUITY RATIO (DER), TOTAL ASSET TURNOVER (TATO), INFLATION AND INTEREST RATE (SBI) ON PROFITABILITY IN CONSTRUCTION COMPANY (PERSERO) ON THE INDONESIA STOCK EXCHANGE - Jeda; Nurlela; Wahyuddin; Husaini (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
This study aims to determine the Debt To Equity Ratio (DER), Total Asset Turnover (TATO), Inflation and Interest Rates (SBI) on Profitability in construction companies (Persero) on the Indonesia Stock Exchange. This study uses secondary data in the form of construction company (Persero) financial reports for 2015-2021 accessed on the company's official website and www.bi.go.id. The population in this study were 22 companies and the sample used was 15 companies selected using the Purposive Sampling method. The results showed that DER had a positive but not significant effect on ROA, TATO had a positive and significant effect on ROA, INF had a positive but not significant effect on ROA, and SBI had a positive and insignificant effect on ROA.